Unsafe haven : the United States, the IRA, and political prisoners - McElrath, Karen, 1959- (Pluto Press, 2000)
Irish political prisoners have sought and found refuge in the United States since the 1800s. In 1986, however, US government policy changed, in part as a reward for Britain's support in the US attack on Libya. The tools of exclusion were subtly and not so subtly politicized, as ways were found to deport or in other ways to criminalize potentially embarrassing Irish activists. In this book, Karen McElrath examines the problematic history of Irish political prisoners in the United States. Drawing on original research interviews with prisoners, their families and their supporters in the US, she looks at the ways in which the rule of law can change, for entirely political reasons" and considers the impact of those changes. She looks too at the use of specific sanctions" deportation, extradition, and prosecution - and at shifting priorities in US immigration policies. In this fascinating account of a complex and much-contested issue, McElrath examines the struggles over deportation and extradition within the context of Anglo-US relations" and sheds new light on the political nature of the rule of law